2022
DOI: 10.3390/pathogens11080920
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Vaccine-like Strain of Lumpy Skin Disease Virus Causes Low-Level Infection of Cattle through Virus-Inoculated Feed

Abstract: Since 1989, lumpy skin disease of cattle (LSD) has spread out of Africa via the Middle East northwards and eastwards into Russia, the Far East and South-East Asia. It is now threatening to become a worldwide pandemic, with Australia possibly next in its path. One of the research gaps on the disease concerns its main mode of transmission, most likely via flying insect vectors such as biting flies or mosquitoes. Direct or indirect contact transmission is possible, but appears to be an inefficient route, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…The LSDV, Saratov/2017, was the first of many novel recombinants between vaccine-derived parental strains to be isolated from active LSD outbreaks in the field in Russia, Kazakhstan and China ( 18 ). Subsequent experiments using Saratov/2017 provided evidence that this recombinant vaccine-like strain is capable of infecting bulls via indirect contact and virus-inoculated feed, i.e., via the alimentary route, thus corroborating its contagious nature and resembling the transmission pathway described in the majority of poxviruses ( 16 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The LSDV, Saratov/2017, was the first of many novel recombinants between vaccine-derived parental strains to be isolated from active LSD outbreaks in the field in Russia, Kazakhstan and China ( 18 ). Subsequent experiments using Saratov/2017 provided evidence that this recombinant vaccine-like strain is capable of infecting bulls via indirect contact and virus-inoculated feed, i.e., via the alimentary route, thus corroborating its contagious nature and resembling the transmission pathway described in the majority of poxviruses ( 16 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 75%
“…It is therefore imperative that the different phenotypic characteristic between the novel recombinant strains as well as the differences between the recombinants and the classical strains be identified in order to link future targeted mutational genotypes to these phenotypes. In a previous experiment, virulent Saratov/2017 with the genomic backbone of a Neethling commercial vaccine, first demonstrated the potential for non-vector borne transmission and in a subsequent study it was shown to cause a mild infection via the alimentary route ( 19 ). By contrast, Udmurtiya/2019 with the genomic backbone of a Kenyan vaccine strain KSGP showed a similar characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Kenyan strains have caused outbreaks in Kenya, but however never been reported in subsequent epidemics in Africa, the Middle East, and Europe (Tulman et al, 2001). Since 2017, recombinant LSDV strains have been detected in infected cattle in Russia (Sprygin et al, 2018;Sprygin et al, 2020;Shumilova et al, 2022); Krotova et al, 2022a), China (Ma et al, 2021), Hongkong (Flannery et al, 2021), Taiwan (Huang et al, 2022) and Vietnam (Mathijs et al, 2021;Tran et al, 2021). In phylogenetic analysis, recombinant strains formed four monophyletic groups R1, R2, R3, and R4 as described in section 3.3.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…These recombinant LSDV strains have demonstrated an increase in virulence as compared to other field LSDV strains and can be transmitted in vector-independent mode (Aleksandr et al, 2020;Kononov et al, 2020). Even, LSDV-Saratov/19 has been demonstrated to persist in winter in absence of vectors through direct contact or fomites (Shumilova et al, 2022). LSDV has also been reported in a giraffe in Vietnam which is closely related to recombinant Vietnamese LSDV strains (Dao et al, 2022).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Lumpy Skin Disease (LSD) is a virus disease of cattle, with significant morbidity and mortality. The disease is characterised by nodular skin lesions evident as lumps along with lymphadenopathy, with severe cases resulting in the death of the affected animal (Shumilova et al, 2022). The morbidity rate in LSD varies widely from 50–100% (Tuppurainen and Oura, 2012).…”
Section: Introductionmentioning
confidence: 99%